Croatia : between Europe and the Balkans - Bartlett, William, 1950- (Postcommunist states and nations, 2003)
Tells the story of Croatia's development since independence, involving rebellion, war and dramatic political, social and economic changes. Addresses developments in economics, politics, international relations and social policy.